Interpolação de imagens baseada em clustering - Akyama, Marcio Teruo (2010)
Image zooming is a task applicable to many areas which can vary from entertainment to scientific applications. A big challenge is image edge preserving without creating artifacts like blurring or blocking. Several methods for edge preserving were proposed in literature. This work presents a new technique proposal based on clustering which aims to increase gray scale image resolution preserving objects edges with a simple method and easy to implement. Many different types of images were used to make tests of the proposed technique and results are compared to classical methods of image interpolation found in literature. PSNR and Cross-Correlation measurements were used to compare efficiency between methods. Results showed that the technique is quite competitive and meets the project goals.